PENGARUH CUKA (ASAP CAIR) TEMPURUNG KELAPA TERHADAP P. palmivora PENYEBAB PENYAKIT BUSUK BUAH PADA KAKAO - Yunita Yunita; Iman Suswanto; Sarbino Sarbino (Perkebunan dan Lahan Tropika, 2021)
Cocoa pod rot disease is one of the important diseases on cocoa crop because they cause substantial losses in crop yields. One method to control spoilage of pod using vinegar (Liquid Smoke) coconut shell. This research aims to obtain a concentration of Vinegar (Liquid Smoke) to suppress the activity of P. pamivora. The study lasted for three months in the laboratory of plant disease Faculty of Agriculture University of Tanjungpura. The method used was Complete Random Design (CRD) with 6 treatment 0%, 5%, 10%, 20%, 40% and fungicides mancozeb 80% active material based on repeated 3 times. The observed parameters is the number of patches and spots, long observations began on the fifth day after incubation. The research results showed that rotten pod disease control using Wood Vinegar is effective at concentrations of 5% and 10% are able to inhibit the activity of P. palmivora.Keywords: Cocoa pod, Vinegar (Asap Cair) Coconut Shell, P. palmivora